Faktor–Faktor Yang Mempengaruhi Cash Holding Pada Perusahaan Sektor Industri Barang Konsumsi - Mentari Dwi Aristi; Melsa Khalida; Zul Azmi (Akuntansi & Ekonomika, 2021)
This study aimed to examine and discover the effect of leverage, capital expenditure, sales growth, and cash flow to cash holding. The population of this study is consumer goods industry company that listed in Indonesia Stock Exchange from 2015 to 2017. The sample selection setting by purposive sampling method and the spesific criteria are as many as 10 companies. The analysis used multiple linear regression. The result show that capital expenditure and sales growth has no effect on cash holding, while leverage and cash flow has negative effect on cash holding. The F test, indicating that the variables of leverage, capital expenditure, sales growth, and cash flow simultaneous has effect on cash holding.